Audit of Attendance Information System with Fingerprint Using Cobit 4.1 Framework at PT DSN - Alda Tasya Salsabilla; Fitri Risca Amrizal Amelya; Rifky Ahmad Sururi; Rochmat Setiyawan (Journal of Social Science, 2022)
The Fingerprint attendance system helps companies control employee working hours more efficiently and improve operational work activities using computerized tools, which can record the attendance list of each company employee. They were conducted following the COBIT Framework 4.1 standards for IT governance. It is necessary to conduct an audit to evaluate the information system's current governance. The research focuses on the sub-domains of AI4, DS1, DS4, DS5, DS10, and ME2. This research uses observation, interview and literature techniques. The data analysis technique used is Maturity level. From the results of the study, it was found that DS5 was at the level of 3.02; DS4 and DS10 were at level 3 (Defined Process); DS1 was at the level of 2.8; AI4 was at level 2.7 (Repeatable but Intuitive); while ME2 is at the level of 1.7 (Initial/ad Hoc). The highest score is on DS5 (Ensure Systems Security) with a value of 3.02, and the lowest is on ME2 (Monitor and Evaluate Internal Control) with a value of 1.7